Potential Benefits of Dynamic Beam Synthesis to Mobile Satellite Communication, Using the Inmarsat 4 Antenna Architecture as a Test Example - R. F. E. Guy (International Journal of Antennas and Propagation)
Present mobile satellite communication systems use large antennas to provide multiple high-gain beams. Each beam covers a fixed geographic cell on the earth. Spatial frequency reuse is provided by synthesising beams with low-power levels over all cells operating at the same frequency. The performance needs for future systems are steadily increasing, leading to higher-gain requirements, which are met by using larger antennas with narrower beams. So the antenna pointing errors become a significant loss factor. An alternative approach is to abandon the use of fixed beams and dynamically synthesise the beams to optimise the antenna performance in real time. This both increases user gain and lowers cofrequency interference whilst also reducing the effects of pointing errors. Simulations, using the Inmarsat 4 antenna architecture as a test example, show that the spatial isolation performance can be significantly improved by using Dynamic Beam Synthesis.